Dynamic expression analysis of Vitelloin‐related genes in Zeugodacus cucurbitae (Coquillett) driven by short‐term high‐temperature stress. Issue 4 (17th January 2022) - Lian, Yuyang; Wang, Aqiang; Yang, Heming; Li, Jinlei; Peng, Sihua; Zhou, Shihao
Abstract: Zeugodacus cucurbitae (Coquillett) is an important pest of fruit and vegetable crops in tropical and subtropical regions. Previous studies have shown that short‐term high‐temperature stress has a significant effect on the oviposition behavior of three successive generations (F1 –F3 ) of Z. cucurbitae (Coquillett). For the clarification of the molecular response of the oviposition behavior of Z. cucurbitae (Coquillett) to short‐term high‐temperature stress, three Vitellogenin ( Vg ) genes, namely, Vg‐1, Vg‐2, and Vg‐3, and one Vitellogenin receptor ( VgR ) gene were selected; 25°C was used as the control treatment; and 33°C, 37°C, 41°C, and 45°C were set as the high‐temperature treatments. Newly emerged adults of the F1 generation were treated for 1 h, and the expression dynamics of the target genes were analyzed 7 days after the emergence of three successive generations of adults. Results showed that the expression of the Vg gene in the 33°C and 37°C groups was upregulated compared with that in the control group, and the difference among the 41°C, 45°C, and control groups was small. VgR gene expression level gradually increased in each treatment group with the increase in the number of days and peaked on Days 6 and 7. Compared with the control group, the expression of VgR gene in the F1 generation was downregulated in the high‐temperature treatment group over 7 days. On Day 7, the expression level of the VgR gene in the F2 and F3 generations in the 37°C and 45°C groups was significantly higher than that in the F2 and F3 generations in the control group. In conclusion, Vg and VgR are transformed and utilized differently after short‐term high‐temperature treatment. Abstract : Dynamic expression analysis of Vitelloin ‐related genes in Zeugodacus cucurbitae (Coquillett) driven by short‐term high‐temperature stress